Dendrite-free and long-life Na metal anode achieved by 3D porous Cu. (20th June 2019) - Sun, Jianchao; Guo, Cuiping; Cai, Yajun; Li, Jingjing; Sun, Xueqin; Shi, Weijie; Ai, Shiyun; Chen, Chengcheng; Jiang, Fuyi
Abstract: Metallic sodium is an ideal anode for high energy batteries because of its low cost, high natural abundance and suitable redox potential. However, the practical application of Na metal in rechargeable Na batteries is seriously limited by uneven Na plating and stripping process during cycling, which leads to Na dendrite formation and low Coulombic efficiencies (CEs). Here, we report that three-dimensional (3D) porous Cu can significantly promote the stability of Na plating/stripping, which features high CEs of 99.4% after 400 cycles at 1 mA cm −2 and low voltage hysteresis voltage (20 mV). Moreover, 3D porous structure provides highly stable and efficient plating/stripping of Na metal up to 6 mA cm −2 . The excellent performance can be attributed to large specific surface area of 3D porous Cu and its good wettability of electrolyte, which is beneficial to actual current density reduction and non-dendritic growth. Due to the superior performance of anode, the full battery coupled with Na3 V2 (PO4 )3 cathode exhibited excellent performance that demonstrates its feasibility in practical applications.